The Role of National Collective Management Institutions in Product Copyright Protection - Nur Azea, Dinda; Agil R, M Andika; Fauzi, Muhammad; Zoish, Sheila; Simamora, Yosua; Dharyan, Yulia (Yayasan Mentari Madani, 2024)
Indonesia, the National Collective Management Institute (LMKN) is responsible for protecting copyright strategically. LMKN's responsibility is to manage copyright for rights holders, especially in the field of music, films, and other works of art. The purpose of this study is to study the role of LMKN in guaranteeing the copyright of creative products in Indonesia and the problems it faces in carrying out its functions. The research was conducted by conducting interviews with copyright law practitioners and other related parties. The results of the study show that LMKN plays an important role in copyright protection. However, there are some issues related to surveillance, royalty sharing, and notifying the Society and industry about these issues